EDUCATION INSTITUTE ADMINISTRATION MODEL FOR EXCELLENCE ACCORDING TO VUDDHIDHAMMA PRINCIPLES OF SCHOOLS UNDER LOCAL ADMINISTRATIVE ORGANIZATIONS PHRANAKHON SI AYUTTHAYA PROVINCE - Kongpibool, Khwanchanok; Dhanapanno, Phramaha Sombat; Thitavaddhano, Phramaha Yannawat (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article was to propose a model of school administration towards excellence based on the principle of four Vuḍḍhi-dhamma of schools under local administrative organizations in Phra Nakhon Si Ayutthaya Province. It was a mixed-method research with 3 research steps: Step 1: Studying the necessity of school administration towards excellence using a questionnaire with a sample of 186 teachers. Data were analyzed using statistics including frequency, percentage, mean, standard deviation, and finding the necessity value. Step 2: Developing the model using interviews with 10 key informants and focus group discussions with 9 experts. Data were analyzed using content analysis. Step 3: Evaluating the model using an evaluation form of a sample of 191 administrators and teachers. Data were analyzed using statistics including frequency, percentage, mean, and standard deviation. The results of the research found that the model of school administration towards excellence based on the principle of four Vuḍḍhi-dhamma of schools under local administrative organizations in Phra Nakhon Si Ayutthaya Province had 5 components, namely principles, objectives, integration, application, evaluation, and evaluation results of the model. Overall, it was at the highest level. When considering each aspect, it was found that the evaluation results were at the highest level in all 4 aspects, namely, usefulness, appropriateness, correctness, and feasibility, respectively. The conclusion was the research knowledge, namely Khwanchanok.